Outcomes of revision surgery for idiopathic macular hole after failed primary vitrectomy - Shi, Yunhong; Feng, Lujia; Li, Yangyang; Jiang, Zhihao; Fang, Dong; Han, Xiaotong; Wang, Lanhua; Wei, Yantao; Zhang, Ting; Zhang, Shaochong (Frontiers in Medicine, 2023)
Persistent idiopathic macular hole (PIMH), the occurrence of idiopathic macular holes that have failed to close after standard pars plana vitrectomy (PPV) with internal limiting membrane (ILM) peeling, has become a global health threat to the aging population. Because postoperative anatomic closure or restoration of visual acuity is more difficult to achieve in PIMH, surgical approaches that would yield the best outcomes remain to be elucidated. On paper, extended ILM peeling combined with silicone oil (SiO) tamponade is believed to be a feasible option for excellent macular hole closure. However, no studies on this combined treatment for PIMH is compared with simple air tamponade have been conducted. Thus, in this retrospective case series, we used spectral-domain optical coherence tomography (SD-OCT) and other technologies to investigate real-world evidence for the anatomical and functional outcomes of revisional PPV with either SiO or air tamponade for failed primary idiopathic macular hole surgery. We included the records of 76 patients with PIMH who had SD-OCT examinations and best-corrected visual acuity (BCVA). Regression analysis was performed to find factors affecting PIMH fracture closure. Seventy-six participants were allocated to a SiO group (n = 21, with an extended ILM peeling and SiO tamponade) or an air group (n = 55, with extended ILM peeling and air tamponade). Anatomical success was achieved in 18 (85.7%) and 40 (72.7%) eyes in the SiO and air groups, respectively (p = 0.37). BCVA was significantly improved in both subgroups of closed PIMH (SiO group: p = 0.041; air group: p < 0.001). Minimum linear diameter (MLD) was closely related to the closure rate (OR, 1.0; 95% CI (0.985–0.999); p = 0.03). MLD = 650 μm seemed like a cut-off point for closure rate (MLD ≤ 650 μm vs. MLD > 650 μm; 88.4% vs. 52%, p = 0.002). In conclusion, we demonstrated that extended ILM peeling combined with SiO or air tamponade is effective in PIMH treatment. Moreover, though not statistically significant herein, the anatomic closure rate was better for silicone-operated eyes than for air-operated eyes. MLD is the best predictor of PIMH closure; MLD ≤ 650 μm could achieve a significantly higher closure rate.